Comparison of Cellular Responses to TGF-β1 and BMP-2 Between Healthy and Torn Tendons. Issue 7 (June 2021) - Morita, Wataru; Snelling, Sarah J.B.; Wheway, Kim; Watkins, Bridget; Appleton, Louise; Murphy, Richard J.; Carr, Andrew J.; Dakin, Stephanie G.
Background: Tendons heal by fibrotic repair, increasing the likelihood of reinjury. Animal tendon injury and overuse models have identified transforming growth factor beta (TGF-β) and bone morphogenetic proteins (BMPs) as growth factors actively involved in the development of fibrosis, by mediating extracellular matrix synthesis and cell differentiation. Purpose: To understand how TGF-β and BMPs contribute to fibrotic processes using tendon-derived cells isolated from healthy and diseased human tendons. Study Design: Controlled laboratory study. Methods: Tendon-derived cells were isolated from patients with a chronic rotator cuff tendon tear (large to massive, diseased) and healthy hamstring tendons of patients undergoing anterior cruciate ligament repair. Isolated cells were incubated with TGF-β1 (10 ng/mL) or BMP-2 (100 ng/mL) for 3 days. Gene expression was measured by real-time quantitative polymerase chain reaction. Cell signaling pathway activation was determined by Western blotting. Results: TGF-β1 treatment induced ACAN mRNA expression in both cell types but less in the diseased compared with healthy cells ( P < .05). BMP-2 treatment induced BGN mRNA expression in healthy but not diseased cells ( P < .01). In the diseased cells, TGF-β1 treatment induced increased ACTA2 mRNA expression ( P < .01) and increased small mothers against decapentaplegic (SMAD) signaling ( P < .05) compared with those of healthy cells. Moreover, BMP-2 treatment induced ACTA2 mRNA expression in the diseased cells only ( P < .05). Conclusion: Diseased tendon–derived cells show reduced expression of the proteoglycans aggrecan and biglycan in response to TGF-β1 and BMP-2 treatments. These same treatments induced enhanced fibrotic differentiation and canonical SMAD cell signaling in diseased compared with healthy cells. Clinical Relevance: Findings from this study suggest that diseased tendon–derived cells respond differently than healthy cells in the presence of TGF-β1 and BMP-2. The altered responses of diseased cells may influence fibrotic repair processes during tendon healing.